Safety, health & environmental hazard identification and risk assessment on warehouse racking installation site / Nurul Izzati Mohamad - Nurul Izzati , Mohamad (2017)
Safety is an important aspect in all business industry. Thus, the employers and employees have equal responsibility towards ensuring a safe workplace. As most people spend at least eight hours of each day at work, working conditions play a major and direct impact on the health and wellbeing of the workers. Occupational accidents will result in economic loss not only to the company but also to the workers as it may lead to permanent disabilities or deaths. Occupational accidents are preventable through implementing effective measures at the workplace. In this study, hazard identification, risk assessment and risk control (HIRARC) were used to evaluate the hazard associated with warehouse racking installation activities following the guideline by Department of Occupational Safety & Health, Malaysia. Hazard at workplace were assessed through site observation, survey questionnaire and interview with key personnel at site. All hazards identified were then quantify with risk rating. Risk matrix is useful for risk analysis that adopt likelihood and severity. The outcome of analysis is good on decision risk control. The results were presented in a HIRARC form and perception of workers were analysis through awareness questionnaire. There was no accident reported only some injuries were experienced by the workers which typical exist include bruises, minor cut and back pain. Keywords: HIRARC, Risk Matrix, Warehouse Racking Installation,